Nanophytosome-functionalized active packaging films for preservation of refrigerated rainbow trout - Mohammad Maleki; Mahmood Alizadeh Sani; Roya Rezaeian-Doloei; David Julian McClements; Mohammad Mohsenzadeh (Food Chemistry: X, 2025)
The application of nanophytosomes in active packaging is an exciting area of research and innovation within food packaging and preservation technologies. Nanophytosomes, which are nanoscale carriers derived from plant extracts, offer several unique properties that enhance the performance of active packaging systems. In this study, nanophytosomes of Perovskia abrotanoides Kar. essential oil (PEO-NP; 10, 20, and 30 mg) and catechin (C-NP; 2.5, 5, and 10 mg) were prepared using the thin layer hydration method. As the nanophytosome concentration increased, the particle size decreased, while the encapsulation efficiency and loading capacity increased. At sufficiently high concentrations, bioactive-loaded nanophytosomes with small mean particle diameters (< 200 nm), low polydispersity indices (≤ 0.2), and negative charges (−34 to −52 mV) could be produced. Transmission electron microscopy images showed that the nanophytosomes were small spherical particles. Encapsulation of the essential oil and catechin within the nanophytosomes improved their stability under refrigerated storage and gastrointestinal conditions. Moreover, the nanophytosome-encapsulated bioactives exhibited greater antioxidant and antibacterial effects than the free ones. Finally, incorporating the bioactive-loaded nanophytosomes into active packaging materials was shown to extend the shelf life of fish fillets, which was attributed to their ability to suppress microbial growth and oxidation. The nanophytosomes developed in this study may therefore be suitable for improving the performance of plant-based preservatives within food and other industries. The incorporation of nanophytosomes into active packaging represents a significant increase forward in food preservation technology. By enhancing delivery mechanisms, improving material properties, and leveraging natural bioactive compounds, nanophytosomes can revolutionize the way food products are packaged and preserved, responding to both market demands and sustainability goals. Further research and development are essential for overcoming challenges related to scalability, regulatory approval, and consumer acceptance.